Digital computational techniques and the laminar flow of a fluid through a helical conduit - Manlapaz, Romeo L. (1968)
This thesis is a study of the feasibility of applying a numerical method of integrating the partial differential equations describing the laminar flow of an incompressible Newtonian fluid through a helical conduit with the aid of an IBM System/360 computer. The relevant partial differential equations are first developed in the appropriate variables and in the appropriate system of coordinates. The partial derivatives in these differential equations are then approximated by finite differences expressions developed from the Taylor series, and the error equations for correcting the assumed values of the dependent variables on the various grid points are set up.